Pelaksanaan Permainan Ular Tangga dalam Kelas Ibu Hamil - Lisda Widianti Longgupa; Nurfatimah Nurfatimah; Nilda Yulita Siregar (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2020)
The efforts to reduce maternal and infant mortality can be done by increasing the coverage and quality of maternal and child health services. One effort is made to bring health services closer to the community through the pregnant mothers class program. Pregnant woman class is a study group of pregnant women with gestational age between 4 weeks to 36 weeks with a maximum number of 10 participants. In this class, pregnant women will learn together, discuss and exchange experiences on overal maternal and child health, facilitated by midwives or health workers by using the class package for pregnant women, namely flip chart, guidelines for implementing classes of pregnant women, class facilitator’s handbook pregnant women, exercise books for pregnant women and books on maternal and child health (MCH). Based on the results of community service activities with participants of 40 pregnant women there was an increase in correct answers to all participants after participating in class activities for snakes ladderss of pregnant women. From the pre-test result it turns out that most of the results obtained were less than 60. This shows that the knowledge ability of pregnant women is still lacking. However, after holding the snakes ladder pregnant class, there was an increase in the knowledge of pregnant women with an increase in the post-test score point in the range between 21-30 (47.5%).